CHANGES IN BODY MASS INDEX IN CHILDHOOD ACUTE LYMPHOBLASTIC LEUKAEMIA PATIENTS DURING TREATMENT AND UP TO 5 YEARS AFTER DIAGNOSIS - Kytömäki, Aino (My University, 2024)
Acute lymphoblastic leukemia (ALL) is the most common cancer type in children. A variety of metabolic and cardiovascular late effects occur commonly in ALL long-term survivors. Previous studies have suggested that ALL long-term survivors are more likely to be overweight or obese than other children and adolescents. The aim of this study was to investigate the development of overweight and obesity during and after ALL treatment. In this single-centre, retrospective study, we assessed the medical records of 115 consecutive children diagnosed with ALL. Weight and height measurements were retrieved from medical records and were used to calculate ISO-BMI, the best available tool for monitoring weight gain in children and adolescents. ISO-BMI was determined at selected time points during treatment and up to 5 years after diagnosis, and the change in mean ISO-BMI was assessed. We compared different treatment protocols, risk groups, age groups and genders to see whether some of these groups are more likely to gain weight than others. In our study, ISO-BMI increased significantly during treatment and during the 5-year follow up. The increase was more significant in high-risk patients compared to standard and intermediate risk patients. Furthermore, the amount of overweight and obese patients increased during the follow-up period whereas the amount of normal weight patients decreased. These results indicate that weight gain is still an issue within ALL patients. This may have a significant impact on ALL survivors’ later health regarding cardiovascular diseases and the development of metabolic syndrome.
Keywords: acute lymphoblastic leukemia, childhood cancer